Formulação não linear de ração para frangos de corte: modelagem e otimização - Almeida, Marcel Alessandro de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The current formulation strategies required the application of new computational tools that use mathematical modelling, supporting decision- making for a precision nutrition. For this reason, non-linear programming, which not only aims to formulate a diet that meets the needs of the animal, according to the minimum cost, but also maximize the profit margin. Thus, the present work had as objective to validate the use of nonlinear principle model (NLP), with maximizing economic returns through performance estimates of birds and feed costs, according to the price change of kg of chicken (average price history for 2009 and 2010), the phases of creation and of sex. Thus, we used 480 broiler chicks, 240 males and 240 females of the same strain (Cobb 500), during the period 1 to 56 days old. The experimental design was completely randomized, with a total of 6 treatments (T1-NLP 50; T2-NLP 25; T3-NLP normal; T4-PNL-25; T5-NLP-50 and T6-PL), with 4 repetitions and 10 birds per plot. The birds were fed ad libitum with experimental rations and water, formulated based on corn, soybean meal, soybean oil, mineral and vitamin supplement, dicalcium phosphate, and limestone. Compliance has been assessed (weight gain, feed conversion and consumption), total energy consumption and profit. It was concluded that the principle of nonlinear formulation is more suitable to meet the concept of precision nutrition for broilers, since the requirements of all nutrients are automatically adjusted by the mathematical model, estimated energy content- related, as distinct nutritional recommendations for stages and ages of broiler, according the program PPFR
Keywords: Ave domestica - Criação; Ave domestica - Alimentação e rações; Controle de custo; Otimização combinatoria; Programação não-linear; Animal feed formulas and receipts